PENGARUH SERVANT LEADERSHIP, MOTIVASI KERJA, DAN BUDAYA KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA DI UNIT PELAKSANA TEKNIS PUSAT PELAYANAN REHABILITASI SOSIAL ANAK INANG MATUTU MAKASSAR - Dewi Rospianti Sumadi; Ilham Safar; Syamsuddin Bidol (Universitas Ichsan Sidenreng Rappang, 2026)
This study analyzes the influence of servant leadership, work motivation, and work culture on the performance of civil servants, both partially and simultaneously. The research uses a quantitative approach with a survey method. The research population is all ASN at UPT PPRSA Inang Matutu, with a saturated sampling sampling technique. Data were collected through questionnaires, observations, and documentation, then analyzed using multiple linear regression. The results of the partial test showed that servant leadership had a positive and significant effect on the performance of ASN (t = 4.009; Sig. = 0.000), while work motivation had no significant effect (t = 0.293; Sig. = 0.771). Work culture has a positive and significant effect on the performance of ASN (t = 5.560; Sig. = 0.000). Simultaneously, the three variables had a significant effect on the performance of ASN (F = 41.622; Sig. = 0.000) with a determination coefficient (R²) of 0.739. This finding confirms that the improvement in ASN performance is stronger determined by strengthening servant leadership and strengthening work culture, while work motivation is not the main determinant in the context of UPT PPRSA Inang Matutu.